Characteristics of HPV Infection in Women Cervical and Anal with HIV-Infected and the Advances in Epidemiological Research - Xiao R; Yang X; Duan R; Zhang H (Infection and Drug Resistance)
Rong Xiao,1,2 Xue Yang,1 Rufei Duan,1 Hongping Zhang1 1Department of Gynecology, The Third Affiliated Hospital of Kunming Medical University, Yunnan Cancer Hospital, Peking University Cancer Hospital Yunnan, Kunming, Yunnan, People’s Republic of China; 2Department of Gynecology, Huize Maternal and Child Health Hospital, Huize, Yunnan, People’s Republic of ChinaCorrespondence: Hongping Zhang, Email kmzhp@126.comAbstract: Antiretroviral therapy (ART) has significantly reduced the incidence and mortality of AIDS-related diseases, bringing the life expectancy of human immunodeficiency virus (HIV)-infected individuals close to that of uninfected individuals. However, the incidence and mortality rates of tumors associated with human papillomavirus (HPV) have not decreased. Persistent infection with high-risk HPV is a major cause of cervical cancer and other related malignancies, and the risk of HPV infection and the incidence of related diseases are higher among HIV-infected individuals. Although the World Health Organization provides screening recommendations for the general population, there is a lack of guidelines for cervical and anal cancer screening specifically in HIV-positive patients. Further research is urgently needed to develop effective preventive measures. This article reviews the epidemiological characteristics and associations of HPV infections and related cancers in HIV-infected women, providing reference for prevention and treatment.Keywords: HIV, HPV, HR-HPV, cervical and anal infection